Динамика наукометрических показателей ученых, сгруппированных в Российском индексе научного цитирования по тематике «Экономика» - Kornienko A. M. (Economic science today: theory and practice, 2016)
based on a database of the Russian Science Citation Index, shows the dynamics of scientometric indicators of scientists, grouped by category "Economy".
Keywords: экономика; динамика; Российский индекс научного цитирования; наукометрические показатели; ученые; scientometric indicators; scientists; Russian Science Citation Index; dynamics; the economy